Penerapan Model Pembelajaran Sinektik Dalam Meningkatkan Keaktifan Belajar Siswa Pada Pelajaran Aqidah Akhlak - chandra, pasmah; Juliansyah; Malisa P. Ningsih (Jurnal Pendidikan Islam Al-Affan, 2021)
The Synectics Model (Synectics) is a learning model designed to develop student creativity. During this time the process of learning morality is still conventional and the student's level of learning during learning is relatively low. So it is necessary to make efforts to improve student learning activities with synectic learning models. This type of research is classroom action research (CAR) with 2 (two) cycles. Data collection tools in this study are, observation, tests and documentation. The data analysis technique in this study was done by performing percentages or comparison of data between cycles I and II. The results of the study are learning by applying the Synectic learning model can increase the learning activeness of fifth grade students of Aqidah Akhlak in MI Nurul Huda Bengkulu City. This can be seen from each cycle (pre cycle, cycle I and cycle II). At the pre-cycle level of student activity only reached 30.55% (very poor), in the first cycle increased to 58.33% (not good) and in the second cycle experienced a significant increase to 83.33% (good).